2023
DOI: 10.1097/mpg.0000000000003875
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ERCP: Factors for Success and Complication—A 17-Year, Multisite Experience

Abstract: Objectives: Endoscopic retrograde cholangiopancreatography (ERCP) is an increasingly utilized procedure in pediatric populations. A lack of dedicated pediatric research has led endoscopists to extrapolate adult risk factors and preventative strategies to children. The aim of this multisite, retrospective study was to identify risks for adverse events, procedure failure, and prolonged courses in pediatric patients undergoing ERCP. Methods: Pediatric pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…These data indicate that children who receive repeat ERCP have a signi cantly higher rate of AEs during their initial ERCP compared to the overall average level, suggesting that AEs are more likely to occur during the initial ERCP in children who receive repeat ERCP. This nding is consistent with the conclusions of a multi-center study on factors related to complications of pediatric ERCP [21].…”
Section: Repeat Ercpsupporting
confidence: 92%
See 1 more Smart Citation
“…These data indicate that children who receive repeat ERCP have a signi cantly higher rate of AEs during their initial ERCP compared to the overall average level, suggesting that AEs are more likely to occur during the initial ERCP in children who receive repeat ERCP. This nding is consistent with the conclusions of a multi-center study on factors related to complications of pediatric ERCP [21].…”
Section: Repeat Ercpsupporting
confidence: 92%
“…These data indicate that biliary obstruction is the main indication for pediatric ERCP, while chronic pancreatitis is the primary disease indication for repeat ERCP. A study suggested that pancreatic diseases such as recurrent pancreatitis, chronic pancreatitis, and pancreatic divisum are closely associated with repeat ERCP > 5 times [21].…”
Section: Disease Distribution Of Pediatric Ercpmentioning
confidence: 99%